Validation of a method for combining biplanar radiography and magnetic resonance imaging to estimate knee cartilage contact. Issue 10 (October 2015) - Thorhauer, Eric; Tashman, Scott
Highlights We validate knee cartilage contact estimation from biplane radiography, CT, and MRI. We compare a physiologic cadaveric model to laser scanning gold standard. Errors in contact area averaged 8.4% for medial and 4.4% for lateral compartment. Amount of applied load did not affect errors. Errors increased with increasing knee flexion angle.